Use of textile fibres in the reinforcement of a gypsum-cork based composite material - Vasconcelos, Graça (2013)
The study presented herein focus on the analysis of a series of experimental tests aiming at characterizing the performance of distinct textile fibers acting as a reinforcement of a gypsum-cork composite material. Two groups of textile fibers were selected, namely synthetic fibers (glass and basalt) and natural fibers (banana and sisal). The reinforced composite material was submitted to distinct types of loading, namely compression tests, which it was possible to obtain the compressive strength and to calculate the elastic modulus, and flexural loading Additionally, aiming at assessing the mode I fracture energy, indirect tests on notched beams were carried out.